Besos para los malditos - Miller, Danny (Crime fiction writer); Jiménez Arribas, Carlos, 1966-; Miller, Danny (Crime fiction writer). (Madrid : Siruela, 2015)
Set in Brighton over the bank holiday weekend of 1964, an ambitious and handsome young detective named Vince Treadwell is sent down to solve a murder and catch the elusive and powerful gangster, Jack Regent. In the tangled web of the crime, Vince falls for Jack's beautiful girlfriend, Bobbie LaVita, and discovers the truth about their own dark pasts.
Online resource; title from ePub title page (Digitalia, viewed March 12, 2016)
Keywords: Gangsters -- England -- Brighton -- Fiction; Organized crime -- Fiction; Nineteen sixties -- Fiction; Electronic books